2010
DOI: 10.4174/jkss.2010.79.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Acute Appendicitis Using Scoring System: Compared with the Alvarado Score

Abstract: Purpose: This study evaluated the usefulness of a new scoring system in diagnosing acute appendicitis which expresses the patient's symptoms, physical examination, and laboratory findings more clearly and objectively. Methods: A prospective study was conducted with 314 patients who were hospitalized with suspicion of acute appendicitis. After analyzing the symptoms, physical examination, and laboratory findings, 10 meaningful variables were selected, each of which were scored separately. The diagnostic value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The same was validated in many studies prior by Sudhir et al and Kim BS et al in their studies. 10,11 Few of the studies which used Alvarado scoring system did not include C reactive protein in the study group and found no difference in the rates of perforated appendix, negative appendectomies and complications between the groups. They also found a delayed appendectomy rate (2 vs 8%) and a lower delayed discharge rate (11 vs 22%) in the group.…”
Section: Discussionmentioning
confidence: 99%
“…The same was validated in many studies prior by Sudhir et al and Kim BS et al in their studies. 10,11 Few of the studies which used Alvarado scoring system did not include C reactive protein in the study group and found no difference in the rates of perforated appendix, negative appendectomies and complications between the groups. They also found a delayed appendectomy rate (2 vs 8%) and a lower delayed discharge rate (11 vs 22%) in the group.…”
Section: Discussionmentioning
confidence: 99%
“…The composite Alvarado scores are categorized as low (0-3), equivocal (4-6), or high (7-10) probability for acute appendicitis. Historically, the Alvarado metric favors specificity over sensitivity, with high positive predictive value (PPV) and diagnostic accuracy for acute appendicitis [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The present study shows that AIR Score has a good statistical discriminating property for diagnosing acute appendicitis with a high sensitivity (78.57%) and specificity (85.71%) when the cut off for diagnosing acute appendicitis was kept at or less than 8 which was similar to other studies done by Frank c, Yang Q etal [14] . When the cut off for diagnosing acute appendicitis by AIR Score was kept at or more than 8 it had a sensitivity of 44% and a high specificity 100% and at this cut off score AIR Scoring cannot be used as a modality to screen patients with acute pain abdomen in Rt Iliac fossa as it is diagnostic of acute appendicitis at a score of 8 and above [15] .…”
Section: Discussionmentioning
confidence: 99%